KEAMANAN DATA PRIBADI DALAM SISTEM PEMBAYARAN E-WALLET TERHADAP ANCAMAN PENIPUAN DAN PENGELABUAN (CYBERCRIME) - Bodhi, Surya; Tan, David (Universitas Ekasakti, 2022)
E-wallet is a digital wallet that is used as a transaction tool in digital form, with the existence of an e-wallet the transaction process is faster and easier in this digitalization era because it only has to scan the QR code. However, behind the efficiency and benefits provided, of course there are risks arising from the use of this e-wallet such as the security of our personal data is threatened. The purpose of this study was to determine law enforcement against cybercrime on e-wallet and protection of personal data on e-wallet. The method used in this research is normative research. Based on the principle of legality of cyber crimes such as data theft has violated the ITE Law, therefore a person's personal data must be protected according to the Regulation of the Minister of Communication and Information and Bank Indonesia. According to Philipus M. Hadjon's theory of legal protection, to overcome legal problems such as data theft on e-wallet, preventive and repressive measures are needed.